Development of Cultural Tourism in Minahasa Regency - Grystin Djein Sumilat,; Xaverius Erick Lobja,; Fonny Rewah, (Technium Social Sciences Journal, 2023)
The existence of culture-based tourism (Cultural Tourism) can be used as an object of tourist attraction that can preserve cultural heritage. Minahasa Regency consists of various cultural attractions to visit, especially during the COVID-19 pandemic that has hit Indonesia since early 2020. The objectives of this study are (1) to Analyze the development of cultural tourism in Minahasa Regency before and after COVID-19. (2) Analyze the adaptation strategy of cultural tourism stakeholders in Minahasa Regency. The data analysis method used by this study is qualitative descriptive and uses SWOT analysis to determine adaptation strategies carried out by stakeholders. The results showed that Bukit Kasih Tourism objects offer a spiritual center, allowing Islam, Catholicism, Protestantism, Hinduism, and Buddhism followers to gather, meditate, and worship. Moraya Fort tourist attraction is a symbol of the struggle and resistance of the Tondano / Minahasa people in resisting colonialism in a monopoly system. Watu Pinawetengan Tourism Object is a cultural historical tourism object about the organization, decision-making, cooperation, and consensus deliberation. The level of accessibility is easy and affordable in these three attractions.